LEARNING TO PRODUCING EXPOSITION TEXT USING PROJECT BASED MODELS IN X CLASS - Eneng Siti Martini; Teti Sobari (IKIP Siliwangi, 2021)
This study aims to describe: (1) effective project-based learning models used in learning to produce exposition text in class X students; (2) project-based models can improve the ability to produce exposition text in class X students; (3) differences in the ability to produce exposition text before and after using a project-based model in class X students. The project-based model is a learning model that stimulates students to be active in solving problems through project activities. The research method used is qualitative descriptive method. The research instruments used, namely lesson plans, tests, observation sheets, and questionnaires that have been analyzed and then concluded. Based on the results of research conducted by the author on class X students, amounting to 25 students before being given the treatment of project-based learning models students get an average value of pretest, which is 68.36. After getting the project-based model treatment the average post-test score was 85.88. It can be concluded that learning to produce exposition text using a project-based model in class X students has proven to be effective and can make students active and learning fun and varied. The observation sheet shows well and the response sheet shows students prefer to use a project based model